Aerosol processing of Ag/TiO2 composite nanoparticles for enhanced photocatalytic water treatment under UV and visible light irradiation. Issue 7 (1st April 2022) - Zhang, Juan; Cha, Jung Keun; Fu, Guiming; Cho, Eun Ji; Kim, Ho Sung; Kim, Soo Hyung
Abstract: In this study, we investigated the effect of Ag addition on the photocatalytic reactivity of TiO2 nanoparticles (NPs). Controlled amounts of Ag were incorporated in TiO2 NPs using aerosol spray pyrolysis and subsequent calcination. Ag/TiO2 composite NPs containing different amounts of Ag (e.g., 0, 0.5, 1, 2, and 5 wt%) were successfully fabricated. The photodegradation performances of the as-prepared Ag/TiO2 composite NPs were tested using methylene blue (MB) solution under UV and visible light irradiation. Upon increasing the Ag content to 1 wt%, the resulting Ag/TiO2 composite NPs exhibited increased photocatalytic reactivity due to lowered bandgap energy, which promoted both charge generation and separation. However, when the Ag content exceeded 1 wt%, the photocatalytic reactivity of the resulting Ag/TiO2 composite NPs was considerably deteriorated due to the masking effect of the excess Ag on the reactive sites of TiO2 . Hence, the incorporation of an optimized amount of Ag in the TiO2 matrix promotes the photocatalytic reactivity of Ag/TiO2 composite NPs by controlling their bandgap energy and charge generation and separation processes. These results could lead to the development of photodegradation active substances for water treatment in organic solutions.